Faktor-Faktor yang Berhubungan dengan Rendahnya Self-efficacy Persalinan Vaginal pada Ibu Hamil Risiko Tinggi di Kota Batam - Susanti Susanti (Jurnal Anestesi, 2025)
Vaginal labor self-efficacy is an important psychological factor that affects the experience and outcome of childbirth, especially in high-risk pregnant women. This study aims to identify factors related to low self-efficacy of vaginal childbirth in Batam City. The observational analytical research design with a cross-sectional approach was carried out on 250 high-risk pregnant women selected through purposive sampling techniques in three health facilities during January–March 2025. The research instruments include the Childbirth Self-efficacy Inventory (CBSEI), Hamilton Anxiety Rating Scale (HARS), Wijma Delivery Expectancy Questionnaire (W-DEQ), Prenatal Social Support Scale, and health worker communication questionnaire. Data analysis used chi-square test and multiple logistic regression. The results showed that 60.8% of respondents had low self-efficacy. The dominant factors associated with low self-efficacy were severe antenatal anxiety (aOR 5.31), fear of childbirth (aOR 4.66), lack of partner support (aOR 4.39), history of sectio caesarea (aOR 3.97), and non-empathic communication of health workers (aOR 3.35). The regression model has a predictive power of 83.6% (Nagelkerke R² = 0.621). Conclusion: the low self-efficacy of vaginal delivery in high-risk pregnant women is influenced by psychological, clinical, social, and health care system factors. Integrated antenatal interventions that emphasize anxiety management, partner support, and empathic communication of health workers are needed to improve the self-efficacy of vaginal delivery.